Insights into the mechanically resilient, well-balanced polymeric membranes by incorporating Rhizophora mucronata derived activated carbon for sustainable wastewater decontamination. (November 2022) - Sherugar, Prajwal; Rao, Srilatha; Kigga, Madhuprasad; George, Sajan D.; Arthi, Manivannan; Déon, Sébastien; Padaki, Mahesh
Abstract: In this study, hydrophilic activated carbon has been prepared and used to synthesize innovative activated carbon/polysulfone mixed matrix membranes (MMMs). These membranes were investigated in terms of membrane morphology, hydrophilicity, antifouling ability, and metal ions rejection. The activated carbon (AC) was prepared from a simple chemical activation method using Rhizophora mucronata propagules, which are rich in aerenchyma cells and possess a high surface area. The hydrophilicity of the MMMs is enhanced by the incorporation of activated carbon, which is confirmed by the measurement of equilibrium water contact angle, water uptake and pure water flux. The optimized concentration of 0.625 wt% activated carbon (A2 ) incorporated mixed matrix membrane exhibits better rejection efficiencies of 98 ± 0.5%, 99 ± 0.5%, 92 ± 2%, and 44 ± 1% for Pb +2, Cd +2, Hg +2, and F − with the permeate flux of 28.27, 31.88, 33.21, 43.82 L/m 2 /h, respectively. The fabricated mixed matrix membranes demonstrated an excellent flux recovery ratio and reversible fouling, when filtrating a mixed feed solution containing 200 ppm BSA, 10 ppm Pb +2 and 10 ppm Cd +2 . The optimized A2 membrane showed excellent long-term stability up to 120 h without compromising in permeate flux and rejection efficiency. Finally, a numerical investigation using a usual transport model has shown that dielectric exclusion was the most probable mechanism that can physically explain experimental trends. Graphical abstract: Image 1 Highlights: Bio-mass derived activated carbon were prepared by Rhizophora mucronata propagules. Novel AC/PSf mixed matrix membranes were fabricated. Impact of AC concentration on membrane productivity and selectivity were studied. Numerical investigation of rejection mechanisms were carried using transport model. Excellent separation efficiency (>99%) and stability (120 h) have been noticed.